2013
DOI: 10.5120/13540-1184
|View full text |Cite
|
Sign up to set email alerts
|

VHDL Realization of Efficient H. 264 Intra Prediction Scheme based on Best Prediction Matrix Mode

Abstract: This paper introduces a VHDL realization of a new efficient intra prediction scheme that aims to enhance the compression efficiency of the H.264 standard. The new proposed algorithm is called Best Prediction Matrix Mode (BPMM). The main idea behind the new prediction scheme is to combine the most usable intra prediction modes, {vertical -horizontal -DC}, into a new efficient prediction mode. The performance of the new proposed prediction scheme with respect to compression ratio, Peak Signal to Noise Ratio (PSN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The key daunting trouble is that we have a high overhead, a result of the existence from 240 to 960 extra bits in each subblock mode would provoke a heavy loss of bandwidth. Accordingly, the decreasing overhead is a bottleneck for (BPMM) in practice [21].…”
Section: Total Overhead = [Num Of Bits For (Prev_mode_flag)×num Of Pi...mentioning
confidence: 99%
See 3 more Smart Citations
“…The key daunting trouble is that we have a high overhead, a result of the existence from 240 to 960 extra bits in each subblock mode would provoke a heavy loss of bandwidth. Accordingly, the decreasing overhead is a bottleneck for (BPMM) in practice [21].…”
Section: Total Overhead = [Num Of Bits For (Prev_mode_flag)×num Of Pi...mentioning
confidence: 99%
“…It should be noted that the best prediction matrix is an excellent substitute of the standard prediction modes and we will rely on it only to achieve the prediction. Further details regarding the proposed algorithm can be found in [9,10]. As shown in Table II the preliminary findings have shown that the (BPMM) had achieved a leading compression ratio with an average of 33.56%.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…The absolute difference module is responsible for calculating the absolute difference values. Finally, the comparator module finds the minimum value of the absolute differences and then selects a value between (upper, left, upper-left corner, and average) that corresponds to this minimum and stores it in the best prediction matrix [24].…”
mentioning
confidence: 99%